2009
DOI: 10.1259/bjr/13797020
|View full text |Cite
|
Sign up to set email alerts
|

Edaravone prevents bowel infarction after acute superior mesenteric artery thromboembolism using autologous fibrin clots in a rabbit model

Abstract: The aim of this study was to evaluate the effects of intra-arterial administration of edaravone after superior mesenteric artery (SMA) thromboembolism in a rabbit model. 24 Japanese white rabbits were randomly allocated to a urokinase group (group U) and a urokinase with edaravone group (group E). A further three rabbits, which were administered an autologous blood clot alone, served as a control group (group C). A 4-Fr sheath was inserted into an SMA. An autologous blood clot was administered to an SMA (group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
8
0

Year Published

2010
2010
2013
2013

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 12 publications
0
8
0
Order By: Relevance
“…I/R-related injuries, which occur when a thrombus is removed, result in marked intestinal tissue damage (40). Oxygen free radicals trigger neutrophil infiltration into ischemic intestinal tissues (41). In rats, edaravone reduced I/R-induced small intestine injury; the levels of intraluminal protein and hemoglobin, which are markers of mucosal injury; TBA-reactive substances and tissue-associated MPO activity; protein and mRNA levels of cytokine-induced neutrophil chemoattractant 1 (CINC-1; a member of the IL-8 family; and intestinal erosion and bleeding (42).…”
Section: Intestinal Injurymentioning
confidence: 99%
See 1 more Smart Citation
“…I/R-related injuries, which occur when a thrombus is removed, result in marked intestinal tissue damage (40). Oxygen free radicals trigger neutrophil infiltration into ischemic intestinal tissues (41). In rats, edaravone reduced I/R-induced small intestine injury; the levels of intraluminal protein and hemoglobin, which are markers of mucosal injury; TBA-reactive substances and tissue-associated MPO activity; protein and mRNA levels of cytokine-induced neutrophil chemoattractant 1 (CINC-1; a member of the IL-8 family; and intestinal erosion and bleeding (42).…”
Section: Intestinal Injurymentioning
confidence: 99%
“…In that study, CINC-1 protein and CINC-1 mRNA levels increased with I/R injury and were reduced by treatment with edaravone. Meanwhile, in rabbits with induced acute superior mesenteric artery thromboembolism using autologous fibrin clots, edaravone was reported to prevent bowel infarction, extend survival time, and reduce mucosal damage (41).…”
Section: Intestinal Injurymentioning
confidence: 99%
“…Animal studies on the mitigation of small intestine damage found that edaravone decreases the degree of I-R-mediated mucosal tissue injury [5][6][7]. Elsewhere, we showed that, in a rabbit ASMAT model that introduced autologous fibrin clots, thrombolysis via the intra-arterial administration of edaravone and urokinase contributed to a reduction in the degree of I-R injury to the small intestinal mucosa [4]. We attributed the failure of edaravone to improve the survival time to inadequate thrombolysis in some areas of the intestinal mucosa and postulated that damage caused by ischaemia rather than reperfusion resulted in critical intestinal injury (e.g.…”
mentioning
confidence: 56%
“…An important factor in the high mortality of ASMAT patients is the generation of active oxygen by ischaemia-reperfusion (I-R) injury. We and others [2][3][4] have reported that the administration of oxygen free radical scavengers, such as superoxide dismutase or dimethylthiourea, reduces the degree of I-R injury in animal models. Edaravone (3-methyl-1-phenyl-2-pyrazolin-5-1; norphenazone; MCI-186), a potent scavenger of hydroxyl and peroxyl radicals, inhibits lipid peroxidation via its antioxidant activity.…”
mentioning
confidence: 92%
See 1 more Smart Citation